Molecular Characterization of Antibiotic Resistant Genes among Gram Negative Clinical Isolates - Ramachandran, Devasena Umai; Sudharsan, Meenambiga Setti (Trends in Sciences, 2022)
Increasing antibiotic resistance is a threat worldwide. Deep studies have to be done for correct and appropriate usage of antibiotics for treating infections efficiently and to curtail the spread of resistance. Hence, this study is aimed at understanding the prevalence of antibiotic resistance genes among 35 gram-negative bacterial isolates. By performing biochemical tests, the isolates were identified to be Escherichia coli (n = 15), Klebsiella oxytoca (n = 3), Klebsiella pneumoniae (n = 5), Proteus mirabilis (n = 4), Proteus vulgaris (n = 1) and Pseudomonas aeruginosa (n = 7). Antibiotic susceptibility tests showed that most E. coli isolates were resistant to ampicillin, levofloxacin and cefazolin. Ampicillin resistance was found in all of Klebsiella oxytoca, Klebsiella pneumoniae and Proteus mirabilis isolates. All Proteus mirabilis isolates were resistant to ciprofloxacin and co-trimoxazole. Pseudomonas aeruginosa showed maximum resistance to gentamycin and tobramycin. All 35 isolates were sensitive to amikacin, imipenem and meropenem. Polymerase Chain Reaction showed that AmpC and SHV genes were predominant in E. coli and Klebsiella species respectively. Among Proteus mirabilis and Pseudomonas aeruginosa, IntI gene was more prevailing. NDM1 gene was not detected in any of the isolates. This study also showed the prevalence of isolates resistant to multiple drugs due to the co-existence of resistant genes. Therefore, control of spread of infections, routine study in this field and proper guidelines for prescribing antibiotics is very necessary. HIGHLIGHTS This study is aimed at understanding the prevalence of antibiotic resistance genes among 35 gram-negative bacterial isolates A considerable number of isolates had antibiotic resistance genes and some isolates showed resistance to multiple drugs due to the co-existence of resistant genes Infections caused by bacteria that are resistant to antibiotics are difficult to treat and may sometimes lead to death Regular study and proper use of antibiotics is essential to curtail the spread of antibiotic resistant bacteria. Regular GRAPHICAL ABSTRACT